2011
DOI: 10.1901/jaba.2011.44-109
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Technology of Derived Stimulus Relations: An Analysis of Articles Published in the Journal of Applied Behavior Analysis, 1992–2009

Abstract: Every article on stimulus equivalence or derived stimulus relations published in the Journal of Applied Behavior Analysis was evaluated in terms of characteristics that are relevant to the development of applied technologies: the type of participants, settings, procedure (automated vs. tabletop), stimuli, and stimulus sensory modality; types of relations targeted and emergent skills demonstrated by participants; and presence versus absence of evaluation of generalization and maintenance. In most respects, publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 46 publications
4
97
0
8
Order By: Relevance
“…The use of the gustatory sensory modality also supported that stimulus equivalence could be trained outside of just verbal to visual stimuli or visual to visual stimuli, which is typically conducted (Rehfeldt, 2011) to train language skills. Though studies have evaluated other sensory modalities by training and testing for successful equivalence (Fienup & Dixon, 2006;Hayes et al, 1988), the current study showed application using an assessment and curriculum guide in the applied setting.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The use of the gustatory sensory modality also supported that stimulus equivalence could be trained outside of just verbal to visual stimuli or visual to visual stimuli, which is typically conducted (Rehfeldt, 2011) to train language skills. Though studies have evaluated other sensory modalities by training and testing for successful equivalence (Fienup & Dixon, 2006;Hayes et al, 1988), the current study showed application using an assessment and curriculum guide in the applied setting.…”
Section: Discussionmentioning
confidence: 92%
“…The stimuli utilized in the 27 studies included pictures, text, letters, numbers, and arbitrary symbols, as well as monetary stimuli (Rehfeldt, 2011). Along with using primarily adolescent participants, all of the previously mentioned studies have exclusively used visual and/or auditory stimuli.…”
mentioning
confidence: 99%
“…De acordo com as sugestões de Cavalcante (1999) e Craveiro (2009), a investigação do controle instrucional em contextos naturais pode auxiliar na ampliação da compreensão de comportamentos verbalmente controlados em diferentes contextos. Outros estudos sobre controle de estímulos também apontam a urgência do desenvolvimento de procedimentos próximos aos contextos naturais (Oliveira & Gil, 2008;Rehfeldt, 2011;Souza & Pontes, 2007;Silva & Souza, 2009). …”
Section: Discussionunclassified
“…El formato C-C es semejante a una interacción conversacional y esto probablemente es más natural que interactuar con la pantalla de un computador. Esta validez ecológica es importante porque puede favorecer la transportabilidad de los hallazgos sobre relaciones derivadas a profesionales encargados de diseñar e implementar programas de intervención y puede favorecer la generalización de los repertorios aprendidos a las interacciones naturales de los participantes (Rehfeldt, 2011).…”
Section: Discussionunclassified